THE HYPOSTASIS OF JESUS AND HIS REFLECTIONS FOR CURRENT BELIEVERS - Andreas Budi Setyobekti (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The emergence of several cults that exist as evidence of the difficulty of understanding the concept of Christology as a whole. Therefore, theologians have tried to explain the concept of Christology using a tool, namely the concept of Hypostasis. The concept of the Hypostasis of Jesus is not easy, especially when describing the person of Jesus in terms of his existence as God and man. It is not too easy to understand the concept. Therefore, researchers are trying to find and see the background of concept building and its implementation for believers. From the background description, the following questions emerge: Is the concept of Jesus Hypostasis able to answer the different views on the divinity and humanity of Jesus? How understand the background concept of Jesus' Hypostasis as a theological struggle and its implementation for believers? The research method used is qualitative by applying the theological systematic analysis method. The results of his research show (i) The background of the emergence of heresies that existed at that time encouraged the emergence of the Jesus Hypostasis Concept as an explanatory model for the Christology concept, especially in explaining the divinity and humanity of Jesus; (ii) the concept of Hypostasis as an answer to the unity of nature between God and man in the person of Jesus, without overlapping nature and how it works; (iii) An effort is needed to explain and implement the concept of Hypostasis to believers.